Contribution of Zubair Hasan to Islamic Economics - Qurroh Ayuniyyah; Hambari; Hilman Hakiem (AL-MUZARA'AH, 2023)
Islamic economics has been growing immensely for almost four decades since the First International Conference on Islamic economics held in Makkah in February 1976. Many improvements on developing Islamic economics as an independent discipline have been done by many scholars. One of the most prominent contemporary scholars who have made some significant work in building Islamic economics by combining the existing modern economics with Islamic teaching is Zubair Hasan. Therefore, the main objective of the study is to provide a summary and analysis of Hasan’s economic thought on Islamic economics. The study is based on secondary data, taken from some books, articles, and journal that Hasan has produced. This study uses a descriptive analysis and employs an inductive approach in tracking and collecting materials and references written by Zubair Hasan from 1975 to 2014. The analytical approach was used to identify Hasan’s thought on several topics in the area of Islamic economics. The study suggests Hasan views on Islamic economics are comprehensive and cover almost all aspects that Islamic economics needs to explain. This includes underlying assumptions, scope of objectives, the role of state and individual, institutional frameworks, distribution, and profit in Islam. His analysis is basically a critical integration between modern economics with Islamic heritage.